Radikalisme dalam Aksi Pergerakan Lingkungan: Studi Kasus terhadap Earth Liberation Front (Periode 1996-2011) - Nirbito, Annisa (UI Scholars Hub, 2013)
Earth Liberation Front (ELF) is an environmental movement which carries out radical direct actions, making it distinct from the mainstream environmental movements which implements peaceful methods in articulating their voices. Although its radical actions encounter negative responses, ELF still uses direct actions as their main tactic. In this writing, the writer seeks to uncover the reasons behind the use of radical actions by ELF. The writer uses three main concepts to arrive at the answer: civil disobedience, violence, and terrorism by Peter Singer; Gaia hypothesis by James Lovelock; and new radicalism in social movements by David Solnit. Through interviews, qualitative content analysis, and network approach, four main reasons behind the use of direct actions by ELF are found: (1) ELF fights for its environmental norms; (2) commitment to uproot capitalist system; (3) urgency to stop environmental degradation; and (4) its actions are aimed to protect the earth. The key finding in this research is anonymity within ELF, which turns out to be the most important aspect for ELF to maintain the sustainability of its movement.